P4_1 High Time - Starkey, David; Nelms, James; Roberts, Declan; Thomas, Suzanne (Physics Special Topics, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–> The paper attempts to determine the differences in the passage of time experienced over an 78.5 year human life span on the surface of earth and atop of the highest peak of Everest. The effects of general and special relativity are investigated. The theory of general relativity shows a difference of 4 hours and 14 minutes, whereas the effects of special relativity are negligible. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>